Spherical aluminum oxide for high-thermal-conductivity pouring sealant and preparation process of spherical aluminum oxide

By using industrial waste aluminum to prepare γ-AlOOH sol and building a thermal conductivity path with silicon nitride fibers and zinc oxide whiskers, the problem of limited thermal conductivity of traditional spherical alumina is solved, and spherical alumina with high thermal conductivity and good particle size distribution is achieved, reducing process costs.

CN120136145APending Publication Date: 2025-06-13JIAN YUSHUN NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510424085.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-07
Publication Date
2025-06-13

AI Technical Summary

Technical Problem

The thermal conductivity of traditional spherical alumina is limited by its intrinsic thermal conductivity, and the high-temperature melt granulation process has high energy consumption and difficult to control the particle size distribution, making it difficult to meet the heat dissipation needs of high-power devices.

Method used

The γ-AlOOH sol was prepared by industrial waste aluminum, and a fiber-spherical thermal conductivity path was constructed with pre-modified silicon nitride fibers and zinc oxide whiskers. Spherification was induced by ultrasonic centrifugal spray drying to obtain spherical alumina with high thermal conductivity.

Benefits of technology

The raw material and process cost are reduced, the thermal conductivity and spherification rate of spherical alumina are improved, and the particle size distribution is good, and the subsequent particle size compounding process is not required, meeting the requirements of high-performance thermally conductive potting adhesives.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120136145A_ABST
    Figure CN120136145A_ABST
Patent Text Reader

Abstract

The invention discloses spherical aluminum oxide for a high-heat-conductivity pouring sealant and a preparation process of the spherical aluminum oxide, and belongs to the technical field of heat-conducting pouring sealants. The process comprises the following steps: firstly, preparing gamma-AlOOH sol by taking industrial waste aluminum as a raw material, and carrying out pre-modification treatment on silicon nitride fibers and zinc oxide whiskers; then adding the modified silicon nitride fibers, zinc oxide whiskers and auxiliaries into the gamma-AlOOH sol, inducing spheroidization through centrifugal spray drying to obtain a spherical precursor, calcining the spherical precursor at 950-1050 DEG C, and converting into alpha-phase spherical particles; and finally, carrying out surface modification on the obtained alpha-phase spherical particles to obtain the spherical aluminum oxide. According to the process, industrial waste is fully utilized, the raw material cost is remarkably reduced, meanwhile, a subsequent particle size compounding process is not needed, the calcination temperature is reduced, the process cost and equipment energy consumption are effectively reduced, and the requirements of the high-performance heat-conducting pouring sealant are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of thermally conductive potting adhesives, and particularly relates to spherical alumina for high-thermal-conductivity potting adhesives and a preparation process thereof. Background Technique

[0002] With the development of technology, people's requirements for electronic products are gradually moving towards high performance and small size; at the same time, with technological progress, the heat dissipation problem has become increasingly serious. Thermally conductive potting adhesives are currently a mainstream core thermal management material, which can effectively improve the heat dissipation efficiency and help maintain the stable operation of electronic devices. Spherical alumina has high phonon conduction ability and low interfacial thermal resistance, and has become one of the main thermal conductive fillers in the field of thermally conductive potting adhesives due to its excellent filling properties and controllable surface characteristics.

[0003] However, traditional spherical alumina is prepared by high-temperature melting granulation, which not only has high energy consumption but also has a wide particle size distribution and is difficult to control, easily affecting the consistency of thermal conductivity. At the same time, the thermal conductivity of spherical alumina is limited by its intrinsic value (25 - 42 W / m·K), and when the filling amount exceeds the critical point, the marginal effect of thermal conductivity improvement is significant, making it difficult to meet the heat dissipation requirements of high-power devices. In response to this, high-thermal-conductivity fillers such as boron nitride (200 - 320 W / m·K) are often used in the field to compound with spherical alumina; but on the one hand, high-thermal-conductivity fillers such as boron nitride are expensive, and on the other hand, co-doping of fillers is likely to cause agglomeration, which will further affect the spheroidization rate and particle size of spherical alumina.

[0004] Based on the above, in order to improve the contradiction between the process cost and performance of spherical alumina for thermally conductive potting adhesives and expand its scope of application, it is of great significance to research and prepare a high-performance spherical alumina for potting adhesives. Summary of the Invention

[0005] Aiming at the problems mentioned in the background technique, the purpose of the present invention is to provide spherical alumina for high-thermal-conductivity potting adhesives and a preparation process thereof. The present invention uses industrial waste aluminum to prepare γ-AlOOH sol, and constructs a fiber-spherical thermal conduction path by combining the obtained γ-AlOOH sol with pre-modified silicon nitride fibers and zinc oxide whiskers. This not only reduces the raw material and process costs, but also the prepared composite spherical alumina has good thermal conductivity and high spheroidization rate. At the same time, there is no need for subsequent particle size compounding process, and the particle size distribution is good.

[0006] To achieve the above object, the present invention specifically adopts the following technical solutions: The present invention provides a preparation process for spherical alumina for high-thermal-conductivity potting adhesives, comprising the following steps: Step 1: Take industrial waste aluminum, dissolve it by acid leaching and remove impurities, and then adjust the pH to obtain γ-AlOOH sol; Step 2: Take silicon nitride fibers and zinc oxide whiskers respectively for pre-modification treatment; Step 3: Add the modified silicon nitride fibers, zinc oxide whiskers and additives obtained in Step 2 into the γ-AlOOH sol obtained in Step 1, and perform ultrasonic treatment. Then, induce spheroidization by centrifugal spray drying to obtain spherical precursors. Place the spherical precursors in a calciner at 950 - 1050 °C for calcination to convert them into α-phase spherical particles; Step 4: Perform surface modification on the obtained α-phase spherical particles to obtain spherical alumina.

[0007] Preferably, the industrial waste aluminum in Step 1 includes at least one of aluminum-containing waste slag and waste liquid, and aluminum alloy cutting waste, and its aluminum content is not less than 90%.

[0008] Preferably, the pH adjustment in Step 1 means first slowly dropping ammonia water until the pH is 4 ± 0.2, then raising the temperature to 60 - 70 °C to adjust the pH to 7.5 - 8.0, and then adding nitric acid to adjust the molar ratio of acid to aluminum to (0.12 - 0.15):1.

[0009] Preferably, the specific steps of the pre-modification treatment of the silicon nitride fibers in Step 2 are: Place the silicon nitride fibers in a silane coupling agent, impregnate, and perform centrifugal drying to obtain pre-modified silicon nitride fibers. Preferably, the diameter of the silicon nitride fibers is 1 - 3 μm and the length is 20 - 50 μm, and the silane coupling agent is γ-aminopropyltriethoxysilane or γ-glycidoxypropyltrimethoxysilane.

[0010] Preferably, the specific steps of the pre-modification treatment of the zinc oxide whiskers in Step 2 are: Ultrasonically disperse the tetrapod zinc oxide whiskers in absolute ethanol, add a titanate coupling agent, stir at a constant temperature, and perform centrifugal drying to obtain pre-modified zinc oxide whiskers. Preferably, the diameter of the tetrapod zinc oxide whiskers is 0.1 - 1 μm and the length is 5 - 10 μm, and the titanate coupling agent is isopropyltri(dioctylpyrophosphato)titanate, and its addition amount is 1% - 2% of the mass of the zinc oxide whiskers.

[0011] Preferably, the addition amounts of the modified silicon nitride fibers and zinc oxide whiskers in Step 3 are 4% - 6.5% and 2% - 4% of the mass of the γ-AlOOH sol, respectively.

[0012] Preferably, the additives in Step 3 are ammonium fluoride and PEG, and their addition amounts are 1.5% - 2.5% and 1% - 2% of the mass of the γ-AlOOH sol, respectively; the power of the ultrasonic treatment is 200 - 400 W, the frequency is 30 - 50 kHz, and the time is 0.5 - 1 h.

[0013] Preferably, the calcination in Step 3 is specifically: First pre-calcine at 600 - 700 °C for 1 - 2 h, and then finally calcine at 950 - 1050 °C for 2 - 4 h. The calcination is carried out under the protection of an inert gas.

[0014] Preferably, the specific steps of surface modification of the α-phase spherical particles in Step 4 are as follows: The α-phase spherical particles are placed in a silane coupling agent, impregnated, and finally centrifuged and cured to obtain modified spherical alumina. Preferably, the silane coupling agent is γ-aminopropyltriethoxysilane or γ-glycidoxypropyltrimethoxysilane.

[0015] The present invention uses industrial waste aluminum as a raw material to prepare γ-AlOOH sol: Both aluminum-containing waste slag and waste liquid, as well as aluminum alloy cutting waste, contain a certain amount of aluminum. The process of the present invention first removes impurities therefrom, and then obtains γ-AlOOH sol by controlling the pH value of the acid leaching solution and the molar ratio of acid to aluminum, which is helpful for the uniform dispersion of subsequent silicon nitride fibers and zinc oxide whiskers and the control of the particle size of spherical alumina.

[0016] Aiming at the problems that the thermal conductivity of traditional spherical alumina is limited and doping boron nitride, etc. will affect the spheroidization rate and particle size, the present invention compositely uses silicon nitride fibers and zinc oxide whiskers to construct a fiber-spherical heat conduction path, where spherical alumina serves as a continuous phase to provide the base thermal conductivity, and silicon nitride fibers and zinc oxide whiskers serve as reinforcing phases to build a long-range heat conduction network. The silicon nitride fibers and zinc oxide whiskers have a low coefficient of thermal expansion, and their fiber whisker structures can form a three-dimensional heat conduction network, and the thermal conductivity of spherical alumina can be effectively improved with a relatively low addition amount. In addition, aiming at the agglomeration problem caused by co-doping, the present invention respectively modifies the silicon nitride fibers and zinc oxide whiskers: The titanate coupling agent can improve the surface activity of zinc oxide whiskers and improve their surface polarity; the silane coupling agent can effectively overcome the problem of reduced dispersibility caused by the easy adsorption of moisture by silicon nitride; the present invention constructs a polarity gradient through corresponding modification treatments to promote the interfacial dispersion between the reinforcing phase and spherical alumina, and finally achieves the purpose of adjusting the particle size of the obtained spherical alumina and improving the thermal conductivity.

[0017] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. For the traditional compounding of spherical alumina particle sizes, it is necessary to precisely control the proportion of different particle sizes, but in actual processes, it is difficult to avoid uneven particle size distribution, which affects the construction of the heat conduction network; based on this, the compounding ratio of particle sizes often needs to be optimized through a large number of experiments, aiming for a large packing density and a low process tolerance. The process of the present invention can control the particle size of the obtained spherical alumina particles. Through particle size detection, it can be known that the particle size of the spherical alumina obtained by the present invention is distributed in the range of 0.5-100 μm, and is concentrated in two intervals of 1-15 μm and 25-90 μm. At the same time, the spheroidization rate ≥97%. There is no need for subsequent particle size compounding process, and its appropriate particle size grading can have better adaptability for filling, achieving a good balance between thixotropy and fluidity.

[0018] 2. Compared with traditional high-temperature melting granulation, the process of the present invention not only makes full use of industrial waste, significantly reduces the raw material cost, but also does not require subsequent particle size compounding process, and reduces the calcination temperature to 950 - 1050 °C, effectively reducing the process cost and equipment energy consumption, meeting the requirements of high-performance thermal conductive potting glue. Description of the Drawings

[0019] Figure 1 It is the particle size classification diagram of spherical alumina prepared in Example 1 of the present invention.

[0020] Figure 2 It is the SEM diagram of spherical alumina prepared in Example 1 of the present invention.

[0021] Figure 3 It is the particle size classification diagram of spherical alumina prepared in Comparative Example 3 of the present invention.

[0022] Figure 4 It is the SEM diagram of spherical alumina prepared in Comparative Example 3 of the present invention. Detailed Description of the Invention

[0023] To make the objectives, technical solutions and advantages of the present invention clearer, the technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments. Those not specified in the embodiments are carried out according to the conventional conditions or the conditions recommended by the manufacturer. Those reagents or instruments not specified in the manufacturer are all conventional products that can be obtained through commercial purchase.

[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the technical field of the present invention. The terms used in the description of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.

[0025] Example 1 A preparation process of spherical alumina for high thermal conductive potting glue, the steps include: 1. Take γ-aminopropyltriethoxysilane and 50% ethanol and mix them at a volume ratio of 9:1, add an appropriate amount of acetic acid to adjust the pH to 4.5, then let it stand for 30 min. Subsequently, immerse the activated (oxygen plasma treatment for 30 min) silicon nitride fiber into the obtained solution (fiber / solution ratio 1:10), stir at a constant temperature of 60 °C for 1 h, and centrifuge and dry to obtain pre-modified silicon nitride fiber. Ultrasonically disperse tetrapod-like zinc oxide whiskers in anhydrous ethanol, add isopropyltri(dioctylpyrophosphato)titanate at 1.5% of the whisker mass, stir at a constant temperature of 70 °C for 1 h, and centrifuge and dry to obtain pre-modified zinc oxide whiskers.

[0026] 2. Remove impurities from waste aluminum cans, then immerse them in nitric acid (2 mol / L) for dissolution (solid-liquid ratio 1:8). Slowly add ammonia water until the pH reaches 4, then raise the temperature to 65 °C and adjust the pH to 7.8. Then add nitric acid to adjust the molar ratio of acid to aluminum to 0.14:1, and stir at 80 °C for 4 h to obtain γ-AlOOH sol. Add 5% of pre-modified silicon nitride fibers, 3% of pre-modified zinc oxide whiskers, 2% of ammonium fluoride, and 1.2% of PEG-6000 by mass of the γ-AlOOH sol, and ultrasonicate (300 W, 40 kHz) for 40 min. After high-speed centrifugation and spray drying, a spherical precursor is obtained. The precursor is pre-calcined at 650 °C for 1.5 h in an argon atmosphere, and then finally calcined at 1020 °C for 3 h to obtain α-phase spherical particles.

[0027] 3. Mix γ-glycidoxypropyltrimethoxysilane with 50% ethanol at a volume ratio of 9:1, add an appropriate amount of acetic acid to adjust the pH to 4.5, and then let it stand for 30 min. Then immerse the above-mentioned α-phase spherical particles in the obtained solution (liquid-solid ratio 8:1), stir at 60 °C for 1 h, centrifuge, and cure at 120 °C to obtain spherical alumina for high thermal conductivity potting adhesive.

[0028] Example 2 A preparation process of spherical alumina for high thermal conductivity potting adhesive, the steps include: 1. Mix γ-aminopropyltriethoxysilane with 50% ethanol at a volume ratio of 9:1, add an appropriate amount of acetic acid to adjust the pH to 4.5, and then let it stand for 30 min. Then immerse the activated (oxygen plasma treatment for 30 min) silicon nitride fibers in the obtained solution (fiber / solution ratio 1:8), stir at a constant temperature of 60 °C for 1 h, and centrifuge and dry to obtain pre-modified silicon nitride fibers. Ultrasonically disperse tetrapod-shaped zinc oxide whiskers in absolute ethanol, add 1% of isopropyltri(dioctylpyrophosphato)titanate by mass of the whiskers, stir at a constant temperature of 70 °C for 1 h, and centrifuge and dry to obtain pre-modified zinc oxide whiskers.

[0029] 2. Remove impurities from waste aluminum cans, then immerse them in nitric acid (2 mol / L) for dissolution (solid-liquid ratio 1:8). Slowly add ammonia water until the pH reaches 4, then raise the temperature to 65 °C and adjust the pH to 7.8. Then add nitric acid to adjust the molar ratio of acid to aluminum to 0.12:1, and stir at 80 °C for 4 h to obtain γ-AlOOH sol. Add 6.5% of pre-modified silicon nitride fibers, 2% of pre-modified zinc oxide whiskers, 2% of ammonium fluoride, and 1.2% of PEG-6000 by mass of the γ-AlOOH sol, and ultrasonicate (300 W, 40 kHz) for 40 min. After high-speed centrifugation and spray drying, a spherical precursor is obtained. The precursor is pre-calcined at 650 °C for 1.5 h in an argon atmosphere, and then finally calcined at 1050 °C for 2 h to obtain α-phase spherical particles.

[0030] 3. Mix γ-glycidyl etheroxypropyltrimethoxysilane with 50% ethanol at a volume ratio of 9:1, add an appropriate amount of acetic acid to adjust the pH to 4.5, then let it stand for 30 min. Subsequently, immerse the above-mentioned α-phase spherical particles into the obtained solution (liquid-solid ratio 8:1), stir at 60 °C for 1 h, centrifuge, and cure at 120 °C to obtain spherical alumina for high thermal conductivity potting adhesive.

[0031] Example 3 A preparation process of spherical alumina for high thermal conductivity potting adhesive, the steps include: 1. Mix γ-aminopropyltriethoxysilane with 50% ethanol at a volume ratio of 9:1, add an appropriate amount of acetic acid to adjust the pH to 4.5, then let it stand for 30 min. Subsequently, immerse the activated (oxygen plasma treatment for 30 min) silicon nitride fiber into the obtained solution (fiber / solution ratio 1:12), stir at a constant temperature of 60 °C for 1 h, centrifuge and dry to obtain pre-modified silicon nitride fiber. Ultrasonically disperse tetrapod-like zinc oxide whiskers in absolute ethanol, add isopropyltri(dioctylpyrophosphato)titanate at 2% of the mass of the whiskers, stir at a constant temperature of 70 °C for 1 h, centrifuge and dry to obtain pre-modified zinc oxide whiskers.

[0032] 2. Remove impurities from waste aluminum cans, then immerse them in nitric acid (2 mol / L) for dissolution (solid-liquid ratio 1:8), slowly add ammonia water until the pH is 4, then raise the temperature to 65 °C and adjust the pH to 7.8, and then add nitric acid to adjust the molar ratio of aluminum to acid to 0.15:1, stir at 80 °C for 4 h to obtain γ-AlOOH sol. Add 4% of the pre-modified silicon nitride fiber, 4% of the pre-modified zinc oxide whiskers, 2% of ammonium fluoride, and 1.2% of PEG-6000 by mass to the γ-AlOOH sol, ultrasonically treat (300 W, 40 kHz) for 40 min, obtain spherical precursors by high-speed centrifugal spray drying, pre-calcine the precursors in an argon atmosphere at 650 °C for 1.5 h, and then finally calcine at 950 °C for 4 h to obtain α-phase spherical particles.

[0033] 3. Mix γ-glycidyl etheroxypropyltrimethoxysilane with 50% ethanol at a volume ratio of 9:1, add an appropriate amount of acetic acid to adjust the pH to 4.5, then let it stand for 30 min. Subsequently, immerse the above-mentioned α-phase spherical particles into the obtained solution (liquid-solid ratio 8:1), stir at 60 °C for 1 h, centrifuge, and cure at 120 °C to obtain spherical alumina for high thermal conductivity potting adhesive.

[0034] Comparative Example 1 Refer to the step parameters of Example 1, the difference is that unmodified silicon nitride fiber is used in step 2.

[0035] Comparative Example 2 Refer to the step parameters of Example 1, the difference is that unmodified zinc oxide whiskers are used in step 2.

[0036] Comparative Example 3 Referring to the step parameters of Example 1, the difference lies in that boron nitride of equal mass is used to replace silicon nitride fiber and zinc oxide whisker in Step 2.

[0037] The spherical alumina samples obtained from the above Examples 1 - 3 and Comparative Examples 1 - 3 were tested, and the results are shown in Table 1.

[0038] Table 1 Detection Results of Spherical Alumina

[0039] It can be seen from Table 1 that the spherical alumina prepared in Examples 1 - 3 of the present invention has a relatively concentrated particle size distribution, a large specific surface area, and a high spheroidization rate. Comparing the detection results of Comparative Examples 1 and 2, it can be known that the pre - modification treatment of silicon nitride fiber and zinc oxide whisker will affect the particle size classification of spherical alumina, and at the same time reduce the specific surface area and spheroidization rate. Comparing the detection results of Comparative Example 3, it can be known that the spherical alumina doped with traditional boron nitride has a wide particle size distribution, a low specific surface area and spheroidization rate, and further particle size compounding treatment is required.

[0040] The spherical alumina prepared in Example 1 and Comparative Example 3 was further analyzed. Figure 1 is the particle size classification diagram of the spherical alumina in Example 1, Figure 2 is the corresponding SEM image; it can be clearly seen that the spherical alumina particles prepared in Example 1 of the present invention have a high spheroidization rate, and the particle size is concentrated in two ranges of 1 - 15 μm and 25 - 90 μm. This particle size distribution can meet a large packing density and has better adaptability for filling, and does not require additional particle size compounding process. Figure 3 is the particle size classification diagram of the spherical alumina in Comparative Example 3, Figure 4 is the corresponding SEM image. By comparison, it can be found that the particle size of the spherical alumina in Comparative Example 3 is concentrated in one range, so subsequent additional particle size compounding treatment is required.

[0041] The spherical alumina obtained from the above Examples 1 - 3 and Comparative Examples 1 - 3 was added to a platinum - catalyzed curable vinyl AB glue, poured into a specific circular groove mold, and cured at 130 °C for 30 min to form an elastic thermal conductive gasket. The thermal conductivity of the material was detected on a thermal conductivity tester (thermocouple type), and the results are shown in Table 2.

[0042] Table 2 Detection Results of Thermal Conductivity

[0043] As can be seen from Table 2, the spherical alumina prepared in Examples 1-3 of the present invention can effectively improve the thermal conductivity of the sample; while the unmodified silicon nitride fibers and zinc oxide whiskers in Comparative Examples 1 and 2 affect the construction of the fiber-spherical three-dimensional thermal conduction network, and the spherical alumina with a wide particle size distribution in Comparative Example 3 affects the consistency of the thermal conductivity performance. Therefore, the thermal conductivity decreases to varying degrees.

[0044] The embodiments described above only represent several preferred embodiments of the present invention. The description is relatively specific and detailed, but it does not limit the present invention. It should be noted that for those skilled in the art, the present invention can also have various changes and modifications. Any modifications, equivalent replacements, improvements, etc. made within the concept and principle of the present invention should be included within the protection scope of the present invention.

Claims

1. A preparation process of spherical alumina for high thermal conductivity potting glue, characterized in that: The steps include: Step 1: dissolving and removing impurities from industrial waste aluminum by acid leaching, and then adjusting the pH to obtain γ-AlOOH sol; Step 2: respectively taking silicon nitride fiber and zinc oxide whisker for pre-modification treatment; Step 3: adding the modified silicon nitride fiber, zinc oxide whisker and additive obtained in step 2 to the γ-AlOOH sol obtained in step 1, and then inducing spheroidization by centrifugal spray drying to obtain a spherical precursor, and calcining the spherical precursor at 950-1050° C. to convert it into α-phase spherical particles; Step 4: Surface modification is performed on the obtained α-phase spherical particles to obtain spherical alumina.

2. The process for preparing spherical alumina for high thermal conductivity potting glue according to claim 1, characterized in that: The industrial waste aluminum described in step 1 includes at least one of aluminum-containing waste slag and waste liquid and aluminum alloy cutting waste, and its aluminum content is not less than 90%.

3. The preparation process of spherical alumina for high thermal conductivity potting glue according to claim 1, characterized in that: The pH adjustment in step 1 refers to first slowly adding ammonia water to a pH of 4±0.2, then heating to 60-70°C to adjust the pH to 7.5-8.0, and then adding nitric acid to adjust the acid-aluminum molar ratio to (0.12-0.15):

1.

4. The preparation process of spherical alumina for high thermal conductivity potting glue according to claim 1, characterized in that: The specific steps of the pre-modification treatment of the silicon nitride fiber in step 2 are: placing the silicon nitride fiber in a silane coupling agent, immersing, and centrifugally drying to obtain the pre-modified silicon nitride fiber.

5. The process for preparing spherical alumina for high thermal conductivity potting glue according to claim 1, characterized in that: The specific steps of the pre-modification treatment of zinc oxide whiskers in step 2 are: ultrasonically dispersing tetrapod-shaped zinc oxide whiskers in anhydrous ethanol, adding titanate coupling agent, stirring at a constant temperature, and centrifugally drying to obtain pre-modified zinc oxide whiskers; the titanate coupling agent is isopropyl tri(dioctyl pyrophosphate) titanate.

6. The process for preparing spherical alumina for high thermal conductivity potting glue according to claim 1, characterized in that: In step 3, the added amounts of the modified silicon nitride fiber and zinc oxide whisker are 4%-6.5% and 2%-4% of the mass of the γ-AlOOH sol, respectively.

7. The process for preparing spherical alumina for high thermal conductivity potting glue according to claim 1, characterized in that: In step 3, the auxiliary agents are ammonium fluoride and PEG, and the addition amounts thereof are 1.5%-2.5% and 1%-2% of the mass of the γ-AlOOH sol, respectively; the power of the ultrasound is 200-400 W, the frequency is 30-50 kHz, and the time is 0.5-1 h.

8. The process for preparing spherical alumina for high thermal conductivity potting glue according to claim 1, characterized in that: The calcination in step 3 is specifically as follows: pre-calcination at 600-700°C for 1-2 h, followed by final calcination at 950-1050°C for 2-4 h, and the calcination is carried out under the protection of inert gas.

9. The process for preparing spherical alumina for high thermal conductivity potting glue according to claim 1, characterized in that: The specific steps of surface modification of the α-phase spherical particles in step 4 are: placing the α-phase spherical particles in a silane coupling agent, immersing, and finally centrifugally solidifying to obtain modified spherical alumina.

10. Spherical alumina for high thermal conductivity potting glue obtained by the preparation process according to any one of claims 1 to 9.